2017
DOI: 10.1038/s41564-017-0063-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of HIV-1 reverse transcripts reveals the multifaceted antiviral functions of APOBEC3G

Abstract: Following cell entry, the RNA genome of HIV-1 is reverse transcribed into double-stranded DNA that ultimately integrates into the host cell genome to establish the provirus. These early phases of infection are notably vulnerable to suppression by a collection of cellular anti-viral effectors, called restriction or resistance factors. The host anti-viral protein APOBEC3G (A3G) antagonizes the early steps of HIV-1 infection through the combined effects of inhibiting viral cDNA production, and cytidine-to-uridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 90 publications
(126 reference statements)
5
105
0
Order By: Relevance
“…A3 enzymes are able to restrict viral replication through deamination-independent mechanisms in addition to the well-characterized deamination-dependent mechanism [73,155,156,169,214,286,294,295]. A3G and A3F delay the initiation of primer extension, which leads to production of less full-length extension products [71,74].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A3 enzymes are able to restrict viral replication through deamination-independent mechanisms in addition to the well-characterized deamination-dependent mechanism [73,155,156,169,214,286,294,295]. A3G and A3F delay the initiation of primer extension, which leads to production of less full-length extension products [71,74].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, A3G can interact with reverse transcriptase directly and inhibit polymerase activity [71,75]. The double-stranded proviral genome is imported into the nucleus and either the uracils cause DNA repair mediated cleavage of the provirus or the provirus is integrated through the action of HIV-1 integrase and host protein interactions [75] (Figure 1.2B, Figure 1.4B).…”
Section: Restriction Of Hiv By Apobec3mentioning
confidence: 99%
See 2 more Smart Citations
“…A3 proteins can also restrict HIV-1 replication via mechanisms other than deamination (e.g. binding the viral RNA or to the viral reverse transcriptase (RT), which reduces vDNA synthesis) [14][15][16][17][18][19][20] . It was previously shown that A3G and A3F can interact with the viral integrase (IN) and RT, but the role of this binding on viral integration is not yet clear [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%